2020
DOI: 10.1016/j.jmgm.2019.107459
|View full text |Cite
|
Sign up to set email alerts
|

Alignment independent 3D-QSAR studies and molecular dynamics simulations for the identification of potent and selective S1P1 receptor agonists

Abstract: a b s t r a c tSphingosine 1-phosphate type 1 (S1P 1 ) receptors are expressed on lymphocytes and regulate immune cells trafficking. Sphingosine 1-phosphate and its analogues cause internalization and degradation of S1P 1 receptors, preventing the auto reactivity of immune cells in the target tissues. It has been shown that S1P 1 receptor agonists such as fingolimod can be suitable candidates for treatment of autoimmune diseases. The current study aimed to generate GRIND-based 3D-QSAR predictive models for ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Translation of the obtained sequence showed that the mutation at position 19is silent while the two others have resulted in missense mutation at the positions 18 (S18G) and nonsense mutation of tryptophan at position 39to stop codon ( Figure 1). Previous studies have shown the variation of amino acid sequence of DOF 4.2-ZF MD simulations have been extensively used to virtually investigate proteinprotein/DNA and protein-small molecules interactions [27][28][29] . Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA 26,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation of the obtained sequence showed that the mutation at position 19is silent while the two others have resulted in missense mutation at the positions 18 (S18G) and nonsense mutation of tryptophan at position 39to stop codon ( Figure 1). Previous studies have shown the variation of amino acid sequence of DOF 4.2-ZF MD simulations have been extensively used to virtually investigate proteinprotein/DNA and protein-small molecules interactions [27][28][29] . Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA 26,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations have been extensively used to virtually investigate protein-protein/DNA and protein-small molecules interactions. 27 - 29 Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA. 26 , 30 , 31 Pandey et al explored the DNA binding ability of DOF domain from wheat showing that single K29R mutation could adversely affect its binding capability.…”
Section: Discussionmentioning
confidence: 99%
“…Using GOLD program, these 21 S1P 1 agonists were docked into S1P 1 according to the procedure explained in our previous work. 19 The binding site for docking was determined based on the coordinates of an inhibitor (namely ML056) co-crystallized with the S1P 1 (PDB ID:3V2Y). ChemPLP scoring function was used for carrying out docking process.…”
Section: Methodsmentioning
confidence: 99%
“…The method developed by Roy et al in DTC Lab 39,40 (https:// dtclab.webs.com/software-tools) was applied for the calculation of applicability domain.…”
Section: Comparative Molecular Field Analysis (Comfa) and Comparative...mentioning
confidence: 99%